Renal adenocarcinoma with marked desmoplasia in a Lion (Panthera Leo): pathomorphological study - Handharyani, Ekowati; Edwar, Syafri; Rumiyati, Endah; Purwandari Kristianingrum, Yuli; Winarto, Adi (Fakultas Kedokteran Hewan Institut Pertanian Bogor, 2014)
Adenocarcinoma is a malignant tumor which characterized by epithelial cells, arrange in tubular, papillary or solid structures. The occurrence of this tumor is rarely reported in wild mammals. A 16-year-old female lion had gradually weight loss and lethargy about one year before death. Treatments were done to rise up the health condition but unfortunately she was death with icteric mucosa. A pathological evaluation on internal organs was done as a regular pathological diagnosis. In a careful investigation the irregular masses were characterized and found in evaluated internal organs such as kidney, heart, and lung. Further evaluation was focus on cellular characterization, which was done using special staining and immunostaining method, to visualize the detail of tissues structure and cell's masses identification.